1963
DOI: 10.1083/jcb.18.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Isolated Nuclei

Abstract: This article describes a method for the isolation of nuclei from guinea pig liver. It involves the homogenization of the tissue in 0.88 M sucrose-1.5 mM CaCl2 followed by centrifugation in a discontinuous density gradient in which the upper phase is the homogenate and the lower phase is 2.2 M sucrose-0.5 mM CaCl2. Based on DNA recovery, the isolated fraction contains 25 to 30 per cent of the nuclei of the original homogenate. Electron microscopical observations showed that ∼88 per cent of the isolated nuclei c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1965
1965
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…We found that this method exactly replicated the high nuclear purity initially reported. The cytoplasmic fraction was saved, and the nuclear fraction was subjected to a nucleolus:nucleoplasm separation protocol (Maggio et al 1963;Muramatsu et al 1963) modified for cultured mammalian cells by our laboratory Pederson 1972, 1973). Total RNA was then isolated from each fraction and analyzed by microarray profiling.…”
Section: Resultsmentioning
confidence: 99%
“…We found that this method exactly replicated the high nuclear purity initially reported. The cytoplasmic fraction was saved, and the nuclear fraction was subjected to a nucleolus:nucleoplasm separation protocol (Maggio et al 1963;Muramatsu et al 1963) modified for cultured mammalian cells by our laboratory Pederson 1972, 1973). Total RNA was then isolated from each fraction and analyzed by microarray profiling.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has already established that the structural features recognized in nuclei in situ are retained in nuclei isolated by aqueous sucrose methods (25,37,38) (see Fig. 1 a).…”
Section: Morphology Of Control and Triton X-io0 Treated Nucleimentioning
confidence: 97%
“…Portions were taken for histological examination, and the rate of dihydrotestosterone formation was measured in 50 mg of slices as described above. Slices (25 mg) were also homogenized in duplicate for the measurement of protein (17), ribonucleic acid (21), and desoxyribonucleic acid (18) as described by Maggio, Siekevitz, and Palade (22).…”
Section: Methodsmentioning
confidence: 99%